ASSOCIATION BETWEEN CULTURAL AWARENESS AND NATIONALISM OF MILLENNIAL GENERATION IN THE DIGITAL ERA - Farikha Fitria Shabrilia; Naomi Enka Maheswari; Theophillus Bagas Adhiatma; Mentari Angela Wahyu Edi Tanaya; Moses Glorino Rumambo Pandin (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Intense exposure to modernization makes the younger generation often not aware that the position of local culture is increasingly being threatened. The purpose of this article is to discuss the cultural awareness of the younger generation and its influence on the nationalism crisis so that later solutions can be found to increase the cultural awareness of the younger generation in the digital era. Researchers used qualitative research methods with a literature study approach and online interviews. As a result, the lack of awareness of the nation's culture has exacerbated the crisis of nationalism among the younger generation. Western culture has made the younger generation forget and not know their native culture. As a result, there is a reluctance to preserve the culture because of the lack of belonging to the culture. This is a sign of an increasing crisis of nationalism.